O eixo oralidade no livro didático : linguagem como prática social - Sipraki, Silvana Aparecida (2015)
This research has as subject the work with the verbal language in the classroom, having as locus of study the activities proposals in three didactic books of 6th grade. It is fitted in the area of Applied Linguistics and is supported in the methodological procedures of qualitative research (MASON, 1996; DENZIN and LINCOLN, 2006; ERICKSON, 1989) and in documentary research (GODOY, 1995; LUDKE and ANDRES, 2013). It aims at investigating the conception of speaking skills in didactic books of 6th grade of Basic Teaching, analyzing three units of different publishing houses and authors, approved by PNLD and used in public schools of Maringá/Pr. The estimated theoreticians who guide the research were based on the book New Literacy Studies (STREET, 1984, 2010, 2014), which recognizes the social uses of the reading and the writing, verifying the literate practices as products of history, culture and speeches. Regarding the speaking skills, it was supported on MARCUSCHI's studies (1997, 2010), since it is observable that the verbal modality of the language must be analyzed in the perspective of the use, as social practice. The results have disclosed that, even though there is an evolution in the linguistic studies regardless this modality of the language, the official documents, like the DCEs that take into account the speaking skills as an axle to be worked, the didactic books have not yet made these theories practical. The analyzed data have shown that, although existing a considerable number of activities that exploit speaking in three LDs analyzed, the verbal approach of the writing and the practices of oratory are still the most recurrent activities, with the proposals of debate, seminary, verbal exposition, genres that are not debatable in books, in relation to its composition, thematic content and style. It can be concluded that further researches contemplating the understanding and the production of verbal genres are indeed necessary and such researches need to describe what constitutes the social speaking skills as practice, so that the school and the LDs can legitimize the speaking skills and the social groups or the people who use speaking and the ones who enable the formation of citizens capable of acting in real social practices.